2013
DOI: 10.1371/journal.pone.0066354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Malaria Vector Control Measures in Urban Settings of Dakar by a Specific Anopheles Salivary Biomarker

Abstract: Standard entomological methods for evaluating the impact of vector control lack sensitivity in low-malaria-risk areas. The detection of human IgG specific to Anopheles gSG6-P1 salivary antigen reflects a direct measure of human–vector contact. This study aimed to assess the effectiveness of a range of vector control measures (VCMs) in urban settings by using this biomarker approach. The study was conducted from October to December 2008 on 2,774 residents of 45 districts of urban Dakar. IgG responses to gSG6-P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 25 publications
3
48
2
Order By: Relevance
“…It is quite conceivable that salivary peptides could complete in the near future, routine thick blood smears performed in the framework of active case detection of malaria infection or in the evaluation of vector control strategies. Indeed, it was shown that it was possible to assess by ELISA, IgG response to gSG6-P1 on eluates of blood drops collected on blotting paper [16,32,33]. This sampling technique could be performed concomitantly to thick blood smears and would allow making several molecular analyses (DNA sequencing of organisms, modern diagnostic techniques based on biomarkers detection.)…”
Section: Discussionmentioning
confidence: 99%
“…It is quite conceivable that salivary peptides could complete in the near future, routine thick blood smears performed in the framework of active case detection of malaria infection or in the evaluation of vector control strategies. Indeed, it was shown that it was possible to assess by ELISA, IgG response to gSG6-P1 on eluates of blood drops collected on blotting paper [16,32,33]. This sampling technique could be performed concomitantly to thick blood smears and would allow making several molecular analyses (DNA sequencing of organisms, modern diagnostic techniques based on biomarkers detection.)…”
Section: Discussionmentioning
confidence: 99%
“…The human IgG response to this protein was validated as serological indicator of exposure to the three main Afrotropical malaria vectors: A. gambiae, Anopheles arabiensis and Anopheles funestus [35e38], and similar results were also obtained using the gSG6-based peptide gSG6-P1 [34,39e42]. In addition, gSG6-P1 has also been employed to evaluate different vector control strategies in Senegal [43] and in Angola [44]. In this last study, a longitudinal evaluation (including parasitological, entomological and immunological assessments) was conducted on children and adults from a malaria-endemic area before and after the introduction of ITNs.…”
Section: Introductionmentioning
confidence: 96%
“…The current trend of "urban malaria" could be maintained due to the increasing worldwide urban population especially in Africa and Asia where malaria is endemic. In such situation, the SB may be a relevant tool through the Gsg6-P1 which has been used to measure the exposure to Anopheles bites in Dakar, a growing city of West Africa and potentially facing to "urban malaria" (Drame et al 2013). …”
Section: Potential Applications To Prognosis Other Diseases or Condimentioning
confidence: 99%